Eksistensi Hukum dalam Penerapan Prinsip Ekowisata Berbasis Masyarakat sebagai Upaya Pelestarian Keanekaragaman Hayati di Indonesia - Nasya Nurul Amalina (Jurnal Hukum Lex Generalis, 2022)
Biodiversity in Indonesia has provided many benefits for the community. Unfortunately, the issue of biodiversity crisis is starting to become dangerous, so efforts to preserve the environment are needed in areas that are in close contact with the community, one of which is tourism. For this reason, the term ‘community-based ecotourism’ principle has now been developed. This principle involves local residents, who have long known and managed various types of resources contained in an ecotourism area, as the main actor in the tourism sector. The recommended form of involvement in implementing this principle is the use of the bottom-up approach and the existence of law in it.